Naval robots and rescue. (13th February 2019) - Sparrow, Robert; McLaughlin, Rob; Howard, Mark
Abstract: The development of unmanned systems (UMS) for naval combat poses a profound challenge to existing conventions regarding the treatment of the shipwrecked and wounded in war at sea. Article 18 of the 1949 Geneva Convention II states that warring parties are required to take "all possible measures" to search for and collect seamen left in the water after each engagement. The authors of the present paper analyze the ethical basis of this convention and argue that the international community should demand that UMS intended for roles in war at sea be provided with the capacity to make some contribution to search and rescue operations.